Mummified precocial bird wings in mid-Cretaceous Burmese amber - Lida Xing (Nature Communications, 2016)
The plumage of Cretaceous birds has previously been described only from compression fossils and isolated feathers in amber. Here, Xing et al.describe two 99 million year old bird wings found preserved in amber, enabling new insight into the evolution of feather arrangement, pigmentation, and structure.